Management of Dupuytren disease of the little finger - Melinda Moscovici; Valerio Pace; Fabrizio Marzano; Francesco Bronzini; Giacomo Placella; Dario Perugia; Nicola Maffulli; Filippo Migliorini; Riccardo Maria Lanzetti (Journal of Orthopaedic Surgery and Research)
Abstract Background The surgical management of Dupuytren disease (DD) is associated with a high rate of complications. Recurrences are relatively common and may result in permanent disability, particularly when the little finger (LF) is involved. This study aims to provide both objective and subjective information, along with professionals’ experiences. Methods A questionnaire survey, comprising both open and closed questions, was distributed to hand surgeons, physiotherapists, and occupational therapists engaged in the management of DD across five continents. The involvement and role of the LF in DD were extensively highlighted and emphasised. Only consistent answers were included. A total of 588 questionnaires were completed. Results 50% (n = 294) of the answers were from hand surgeons, 24% (n = 141) from physiotherapists and 26% (n = 153) from occupational therapists. 76.5% (n = 153) of the healthcare professionals (HCP) agreed that: “The LF does not necessarily benefit from good results. Rehabilitation, just like surgery, can be delicate and difficult.”. Different agreements were found between surgeons and occupational therapists (p = 0.007) and among surgeons, depending on their surgical experience (p = 0.008). No significant differences were seen between surgeons and physiotherapists. Conclusions The LF in Dupuytren’s disease requires special attention during surgery and rehabilitation. All healthcare professionals (HCPs) should invest in patient education to ensure early referral and optimal adherence to treatments. Further high-quality research is warranted to achieve a definitive consensus on optimal treatment and rehabilitation.